THE EFFECT OF PROBLEM BASED LEARNING MODEL ON CREATIVE THINKING OF STUDENTS - Widiyaningrum Kurniasari; Edi Purwanta (Borys Grinchenko Kyiv Metropolitan University, 2019)
The aim in this research article is to test the effect of the problem based learning model on the creative thinking abilities of fourth grade elementary school students. The study was conducted using a quantitative approach to the type of experimental research. The sample used in this study was fourth grade students at Kateguhan 02 Elementary School and 02 Corner Elementary School. The instrument used was a test inventory. The results obtained were analyzed using one way ANOVA using SPSS program assistance. The results obtained in this study indicate that there is a positive and significant influence on the Problem Based Learning model on the creative thinking of fourth grade elementary school students. Test results using one way ANOVA showed an F-value of 55,329 and p 0,000 <0.05.